The Effect of Transformational Leadership and Technological Literacy on Increasing Teacher Innovativeness - Lasrin, Herman; Rubini, Bibin; Novita, Lina (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to analyze the influence of transformational leadership and technology literacy on teacher innovation in secondary schools, and to explore the synergy between the two in encouraging learning innovation. Using a mixed-methods approach with a convergent parallel design, quantitative data were collected through a survey of 127 teachers and school principals in Bogor City. In contrast, qualitative data were obtained through in-depth interviews with 10 informants. The SEM-PLS analysis showed that transformational leadership had a significant effect on teachers' innovation (β = 0.383; p < 0.001), followed by technology literacy (β = 0.269; p < 0.001). Qualitative data reinforce these results by revealing that moral support, experimental space, and digital skills are important combinations in realizing creative ideas. Data integration shows that teacher innovation is not born from a single factor, but rather from the synergy between a supportive leadership climate and adequate technological capacity. These findings expand the theoretical understanding of leadership in digital education and highlight the need for visionary leadership training and digital literacy to foster sustainable innovation, especially in Islamic schools.